High-velocity string of knots in the outburst of the planetary nebula Hb4. Issue 3 (7th February 2019) - Derlopa, S; Akras, S; Boumis, P; Steffen, W
Abstract: The bipolar collimated outflows of the Hb4 planetary nebula (PN) exhibit an evident decrease in their expansion velocity with respect to the distance from the central star. So far, similar velocity law has also been found in Herbig–Haro objects. The interpretation of this peculiar velocity law and the classification of the outflows is the main focal point of this paper. High-dispersion long-slit echelle spectra along with high-resolution images from the Hubble Space Telescope ( HST ) are applied in the astronomical code shape in order to reproduce a three-dimensional morpho-kinematical model for the core and the bipolar outflows. Its central part shows a number of low-ionization filamentary structures (knots and jets) indicative of common-envelope PN evolution and it is reconstructed assuming a toroidal structure. The high-resolution HST [N ii] image of Hb4 unveils the fragmented structure of outflows. The northern and southern outflows are composed of four and three knots, respectively, and each knot moves outwards with its own expansion velocity. These are reconstructed as a string of knots rather than jets.This string of knots is formed by ejection events repeated every 200–250 yr. Hb4 displays indirect evidence of a binary central system with a Wolf–Rayet companion evolved through the common envelopes channel. The observed deceleration of the knots is likely to be associated with shock collisions between the knots and the interstellar medium or nebular material.